One missing value problem in Latin square design of any order: Exact analysis of variance. Issue 1 (1st January 2017) - Sirikasemsuk, Kittiwat; Leerojanaprapa, Kanogkan
Abstract: This research proposes a simplified exact approach based on the general linear model for solving the K  ×  K Latin square design (LSD) with one replicate and one missing value, given the lack of ready-made mathematical formulas for the sub-variance. Under the proposed scheme, the effects of the potential variable were determined by means of the regression sums of squares under the full and reduced treatment models. The mathematical expressions could be applied to the LSD with one missing value of any order. Moreover, the treatment, row and column sums of squares are unbiased.